2015
DOI: 10.1589/jpts.10.3141
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between distribution of body fat mass and carotid artery intima-media thickness in Korean older adults

Abstract: [Purpose] The aim of this study was to examine the relationships between the amount and distribution of body fat and the carotid intima-media thickness to explore whether coronary artery disease risk may be mediated through effects on the amount of fat mass in older adults. [Subjects and Methods] A total of 200 elderly females was participated. The percentage of body fat mass was measured by the bioelectrical impedance analysis method, and the carotid intima-media thickness was measured by B-mode ultrasound. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
4
5
0
Order By: Relevance
“…Our finding that various adiposity phenotypes were associated with greater CIMT in both women and men expands the evidence on this matter since it has been previously reported in European, American, African–American and Asian populations [ 17 18 19 37 38 ]. In our study, BMI showed a stronger association with CIMT compared to the other measures of adiposity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our finding that various adiposity phenotypes were associated with greater CIMT in both women and men expands the evidence on this matter since it has been previously reported in European, American, African–American and Asian populations [ 17 18 19 37 38 ]. In our study, BMI showed a stronger association with CIMT compared to the other measures of adiposity.…”
Section: Discussionsupporting
confidence: 87%
“…Extensive research has shown that common CIMT, assessed using B-mode ultrasonography, is a marker of the presence of atherosclerosis locally and elsewhere in the arterial system, and, as such, is an intermediate stage for the development of CVDs [ 14 15 16 ]. However, most of the research examining the relationship of adiposity with atherosclerosis, assessed using common CIMT has been conducted in Whites [ 17 ], Asians [ 18 19 20 ] and African–Americans [ 21 ] from high income countries, but little information is available for black African populations from SSA.…”
Section: Introductionmentioning
confidence: 99%
“…CIMT correlates with BMI and WC/WHtR in children and adolescents [ 22 ], in middle-aged adults [ 23 ], and in older adults [ 24 ]. In a sample of Korean older women, Park et al [ 25 ] also showed overweight and obese women had significantly higher risks of subclinical atherosclerosis (OR=3.033, 95%CI=1.064-8.650 and OR=2.459, 95%CI= 0.998-6.059, respectively) after adjustments for age, height, systolic blood pressure, physical activity level, and total cholesterol level, as compared with optimal weight women. In addition, central obesity was found to be more closely associated with an abnormally increased CIMT in middle-aged and elderly Chinese [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that there was no association of overall obesity or visceral obesity with the presence of carotid plaque [20,21]. Research by Kim Tae Nyun et al showed the ratio of muscle to fat to be associated with arterial stiffness [22].…”
Section: Introductionmentioning
confidence: 99%